White Blood Cell Counts to High-Density Lipoprotein Cholesterol Ratio, as a Novel Predictor of Long-Term Adverse Outcomes in Patients After Percutaneous Coronary Intervention: A Retrospective Cohort Study - Wu, Ting-Ting; Zheng, Ying-Ying; Xiu, Wen-Juan; Wang, Wan-Rong; Xun, Yi-Li; Ma, Yan-Yan; Kadir, Patigvl; Pan, Ying; Ma, Yi-Tong; Xie, Xiang (Frontiers in Cardiovascular Medicine, 2021)
Background: White blood cell counts (WBC) and high-density lipoprotein cholesterol (HDL-C) are widely available in clinical practice. However, the predictive value for cardiovascular disease (CVD) is uncertain.In the present study, we firstly assessed the prognostic value of WBC to HDL-C ratio (WHR) in patients with coronary artery disease (CAD) who underwent percutaneous coronary intervention (PCI). Methods: 5679 patients with CAD after PCI from a retrospective cohort study (identifier: ChiCTR-INR-16010153) were evaluated finally.The primary outcome was long-term mortality. Secondary endpoints were mainly major adverse cardiovascular and cerebrovascular events (MACCEs) defined as a combination of stroke, cardiac death, stent thrombosis, recurrent myocardial infarction, and target vessel revascularization. The mean follow-up time of this study was 35.9± 22.5 months. We defined the best cut-off value of MAR according to the receiver operating curve (ROC), and then patients were divided into high and low WHR groups according to the cut-off value. We analyzed the data in both acute coronary syndrom (ACS) and stable CAD subgroup, respectively. Results: Overall, there were 293 long-term mortality during the follow-up period. According to the cut-off value (WHR=8.25), 1901 ACS patients were divided into high WHR group (n=724) and low WHR group (n=1177). Compared to low WHR group, the incidence of all-cause mortality (ACM, 5.5% vs. 3.6%, P=0.048) and cardiac death (4.7% vs. 2.9%, P=0.042) were significantly higher in the high WHR group. In stabel CAD group, we also found the incidence of ACM and cardiac death were significantly higher in the high group compared to that in the low group. We did not found significant difference between the high and the low WHR group in the incidence of MACCEs.The multivariate Cox proportional hazards model showed that increased WHR level was independently correlated with the mortality. In the high WHR group, the risk of ACM increased two times in ACS [adjusted HR=2.036 (1.258-3.296), P=0.004] and 1.5 times in stable CAD [adjusted HR=1.586 (1.178-2.136), P=0.002]. Conclusion: The present study indicated that increased white blood cell counts to high-density lipoprotein cholesterol ratio was independently associated with long-term mortality in CAD patients who underwent PCI.